Importance of EU regional support programmes for firm performance. (17th May 2019) - Beņkovskis, Konstantīns; Tkačevs, Oļegs; Yashiro, Naomitsu
Summary: This paper investigates the effects of EU regional support on firm productivity, the number of employees and other performance indicators. We use a rich firm-level dataset for Latvia – the country, where investment activities are largely affected by the availability of EU funding. After controlling for the fact that more productive and larger firms are more likely to acquire EU finds, we find that participation in projects co-financed by the European Regional Development Fund (ERDF) increases firms' employment, turnover and capital stock per employee immediately, while it raises their productivity only two years after the launch of the projects. ERDF beneficiaries that are initially less productive, larger, less capital intensive and more financially leveraged enjoy larger productivity gains.